Youth Knowledge and Attitudes about Sex Education in SMA PGRI Waingapu, East Sumba Regency - Martha Meti Kodi; Maria Christina Endang Sukartiningsih; Devita Nila Turupaita (JURNAL KESEHATAN PRIMER, 2018)
Background: Sex education is one way to reduce or prevent sex abuse, especially to prevent unexpected negative effects such as unplanned pregnancies, sexually transmitted diseases, depression and feelings of sin, through sex education, children are easy to make decisions that related to their sexual health problems and taught to be a responsible person. Sex education is education about life. The purpose of this study was to determine the description of adolescent knowledge and adolescent attitudes about sex education in adolescents of class XI in SMA PGRI Waingapu. Method: The type of research used is deskritive sampling techniques accidental sampling, the sample size in this study amounted to 99 people. The instrument of this study used a questionnaire. Results: research conducted on 99 respondents in the knowledge variable found 62 people (62.62%) who were well-informed while in the attitude variable there were 52 people (52.52%) who were quite good. Conclusion: It can be concluded that there is an influence of sex education on the level of knowledge and attitudes of adolescents in preventing free sex. Researchers suggest that the school collaborate with health institutions that can increase adolescent knowledge and attitudes about sex education so as not to cause undesirable effects.